GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP WARIA TENTANG INFEKSI MENULAR SEKSUAL DI KOTA PONTIANAK TAHUN 2014 - ., Joko Herdiyanto (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: sexually Transmitted Infections (STIs) remain as acurrent health problem, affecting both social and economic sectors invarious countries.STIs. Sexual behavior of tranvetite group had highimpact to spreading of STIs because their sexual relation generallyhave  high risk  because  often  flitting  of  couple. Objective: theresearch aimed to find out the level of knowledge and attitude oftranssexual in Pontianak city towards STis. Method: the research wasdescriptive and was conducted with cross-sectional approach surveymethod. The research population was the entire . A total of 55 sampleswere collected. Sampling was conducted through concecutivesampling technique. Data was collected using questionnaires and thenanalyzed by using descriptive statistic method. Results: the result ofstudy show that the level of knowledge and and attitude towards STIsis categorized as sufficient. Conclusion: Therefore, as shown in theresult of the study, it is trongly recommended that both the HealthService and community could work together in educating the studentsregarding STIs issue as well as sex education concurrently.Keyword: knowledge, Attitude, Transsexual, Sexual TransmittedinfectionMedical School, Faculty of Medicine, University of TanjungpuraPontianak, West Borneo.1)Faculty of Medicine, University of Tanjungpura Pontianak, WestBorneo.2)Public Health Department, Faculty of Medicine, University ofTanjungpura Pontianak, West Borneo.3)Department of Dermatovenerology, Faculty ofMedicine,Tanjungpura University, Pontianak, West Borneo